New Late Pleistocene megafaunal assemblage with well-supported chronology from the Pampas of southern South America - Scanferla, Agustín (2013)
Late Pleistocene outcrops exposed in Buenos Aires province, Argentina, represent one of the most informative sources about the paleoecology of South American megafauna. However, there are no records of an accurately dated carnivore–herbivore taphocenosis. This paper presents preliminary results of a recent excavation at the margins of the Salado River, on sediments attributed to the Luján Formation (Late Pleistocene–Early Holocene). The fossiliferous strata consist of greenish brown sandy-clays deposited in a small paleopond environment that was filled by fluvial sediments, exhibiting abundant organic matter, gypsum and carbonate concretions. Fieldwork yielded an association of extinct large-sized mammals that include the horseHippidion principale,the saber-tooth catSmilodon populator(at least one adult and one juvenile associated specimen), a giant ground slothMegatherium americanum, and the glyptodontDoedicurus clavicaudatus. Four14C dates were performed on organic matter (12,100±10014CBP), a femur ofS. populator(13,400±20014CBP), and a cervical vertebra ofHippidion principale(12,860±12014CBP), and a pelvis ofD. clavicaudatus(12,380±19014CBP) situating the site within 12,500 and 13,500 years, approximately. Remarkably, some of the recovered specimens exhibit conspicuous bone modifications (furrows, pits, punctures, striations and crenulated margins) attributed to the activity of a medium-large carnivore. The association between bones of herbivore mammals with conspicuous modifications produced by a large carnivore, and the presence of cub and adult remains ofSmilodon, link this felid with at least part of the excavated association.